Knowledge about Alzheimer's disease in the Brazilian population - Daniel Krempel Amado; Sonia Maria Dozzi Brucki (Arquivos de Neuro-Psiquiatria)
ABSTRACT Dementia is a very common disease, but the general population's knowledge about its main etiology, Alzheimer's disease (AD), is still poor, leading to delayed seeking of healthcare services, less prevention of disease by lifestyle changes and more difficulty in managing the care of the demented. Objective: To measure knowledge about AD in a Brazilian sample, taking into account some demographic variables. Methods: A link to a self-administered online questionnaire was sent by email and via other social media to anyone older than 18 years old. Our questionnaire contained sociodemographic questions and the Alzheimer's Disease Knowledge Scale (ADKS), a well-established scale comprising 30 “true or false” questions about AD. Results: 1,414 people (1,076 females), with a mean age of 42.3 years (SD ± 14.1), and 87.4% having more than 11 years of schooling, answered the online questionnaire. The mean total score for the ADKS was 21.6 out of 30 points (SD ± 3.73); however when we excluded health professionals (36.4% of the sample), it dropped to 20.5/30 (SD ± 3.51). The scores were positively influenced by educational level, professional skills (better for health professionals, mainly physicians) and by age (younger than 65 years). Being a caregiver or family member did not influence the knowledge about disease. Discussion: Despite the high prevalence of AD, few studies have been conducted in Brazil regarding the population's knowledge about the disease. Our study revealed a lack of information about AD in our country, even in relatives and caregivers of demented patients.